2014
DOI: 10.1111/bjd.13069
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic criteria associated with BRAF and NRAS mutation status in primary cutaneous melanoma

Abstract: This study showed a correlation between BRAF and NRAS status and dermoscopic findings of 'peppering' as an expression of regression and melanophages in the dermis, suggesting a morphological consequence of immune behaviour in BRAF-mutated melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…Dermoscopic features have been associated with genetic alteration, while few studies have been conducted to identify a correlation between BRAF mutational status of melanomas and their dermoscopic or confocal microscopy substrates …”
Section: Introductionmentioning
confidence: 99%
“…Dermoscopic features have been associated with genetic alteration, while few studies have been conducted to identify a correlation between BRAF mutational status of melanomas and their dermoscopic or confocal microscopy substrates …”
Section: Introductionmentioning
confidence: 99%
“…In particular, melanomas with common genetic mutations might share certain morphological features detectable with the noninvasive diagnostic tools used widely in common clinical practice in selected centers, such as dermoscopy and reflectance confocal microscopy (RCM). Recently published scientific articles have reported the analysis of the main dermoscopic differences in melanocytic lesions with certain genetic mutations in some research centers [6][7][8], but the use of RCM has not been reported before. In particular, Pozzobon et al [7] found that 'peppering', the dermoscopic pattern expressing regression and the presence of melanophages in the dermis, is the most common dermoscopic pattern in BRAF mutated melanomas compared with wild-type melanocytic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published scientific articles have reported the analysis of the main dermoscopic differences in melanocytic lesions with certain genetic mutations in some research centers [6][7][8], but the use of RCM has not been reported before. In particular, Pozzobon et al [7] found that 'peppering', the dermoscopic pattern expressing regression and the presence of melanophages in the dermis, is the most common dermoscopic pattern in BRAF mutated melanomas compared with wild-type melanocytic cancer. We present our preliminary personal experience in the evaluation of BRAFV600E mutated melanomas with RCM compared with wild-type melanomas matched for age, sex, and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that approximately 50% of melanomas have a BRAF V600 mutation [3]. Few recent studies have sought to correlate BRAF mutational status with features observed via non-invasive evaluation techniques, such as dermoscopy [4,5,6]. Researches have noted that BRAF mutated melanomas tend to be of the superficial spreading type and often reveal peppering on dermoscopy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Few recent studies have sought to correlate BRAF mutational status with features observed via non-invasive evaluation techniques, such as dermoscopy [4,5,6]. Researches have noted that BRAF mutated melanomas tend to be of the superficial spreading type and often reveal peppering on dermoscopy [5]. Ruini et al used Reflectance Confocal Microscopy (RCM) to evaluate 8 melanomas and suggested that RCM may provide more specific information on the cytoarchitectural structure of BRAF mutated melanomas [7].…”
Section: Introductionmentioning
confidence: 99%